TEACHING STUDENTS TO INDEPENDENT CREATIVE THINKING (International journal of artificial intelligence, 2024)
The need for highly qualified specialists is increasing as a result of identifying the inextricable aspects of general secondary education with production. Improvement of teaching methods at the time of this need is from important qualities to connect the continuity of educational theory with practice and the principles of didactics such as science, systematicity, sequence, consistency and exhibitionism.